Pemberdayaan Masyarakat Melalui Program Tanaman Obat Keluarga (TOGA) di Murangan VIII Triharjo - Amrin, Ananda Nasywa; Fhara Nur Aulia Azzahra; Miftahul Muflihah; Fariskayuni; Syahidatul Jannah; Raodahtul Jannah; Fitriani Nur (Faculty of Tarbiyah and Teacher Training, 2026)
Utilization of yard land thru the cultivation of Family Medicinal Plants (TOGA) has become one of the strategies for family health independence. However, the community of RW 29, Desa Murangan VIII, Kelurahan Triharjo, Kecamatan Sleman is facing the problem of declining utilization of traditional medicinal plants despite the availability of land with potential for development. Therefore, this program aims to improve health literacy and community independence thru the development of Family Medicinal Plants (TOGA). The method used is health education and community empowerment based on the environment with a participatory approach, involving students and the Family Welfare Program (PKK). Activities were carried out thru observation, seed procurement, land clearing, planting, and socializing the benefits of TOGA using brochures. The results of the activities show that the vacant land was successfully transformed into a TOGA garden as a center for medicinal plants. In addition, this program raises public awareness about the importance of utilizing medicinal plants in maintaining community health. Thus, the development of TOGA not only supports the independence of public health but also has the potential to increase the productivity of the local community.